As atividades circenses e a formação continuada de professores: análise de um processo - Sanches, Jonathan Wagner Ramos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Circus activities have formed over the years as an important content to be exploited by the teachers in the school environment, and current projections, the inclusion of circus activities in physical education classes has been presented and defended by several authors. That being so, the objective was to offer a continuing education program thematising circus activities having as research focused on the analysis of this training process, as well as their implications, contributions, opportunities and challenges for teacher pedagogical practice. The research, qualitative, was developed in two phases: a questionnaire for physical education teachers working in public schools in order to highlight the reasons for the absence of most of the teachers in the training program. The second phase included the development of the continuing education program content circus activities in the continuing education of physical education teachers, the two teachers in the school environment, as well as analysis and reflection of teacher participation in the training program, described in daily class and daily meetings ending this step with a final interview. Participated in the study, 13 physical education teachers of the municipal school system of a city of São Paulo, of which only two teachers participated in the development of the training program in schools. The teachers manifestations through the questionnaire and participation in the training program showed that teachers make themselves available to participate in continuing education programs, however, the priorities of each teacher (such as family, leisure or other chores) can demarcate difficulties in establishing common to all teachers moments, preventing the effective participation of teachers within the continuing education programs. On the other hand, the school is set up as a rich space of experiences and exchanges of experience, contributing to the development of continuing education programs

As atividades circenses vêm se constituindo ao longo dos anos como um importante conteúdo a ser explorado pelos professores no ambiente escolar, e no cenário atual, a inclusão das atividades circenses nas aulas de Educação Física vem sendo apresentada e defendida por diversos autores. Em sendo assim, o objetivo deste trabalho foi oferecer um programa de formação continuada tematizando as atividades circenses tendo como foco de investigação a análise deste processo formativo, bem como, suas implicações, contribuições, possibilidades e desafios para a prática pedagógica docente. A pesquisa, de natureza qualitativa, foi desenvolvida em duas fases: aplicação de questionário aos professores de Educação Física atuantes da rede municipal de ensino com o intuito de evidenciar os motivos da ausência da maioria dos docentes no programa formativo. A segunda fase contemplou o desenvolvimento do programa de formação continuada o conteúdo atividades circenses na formação continuada de professores de Educação Física, a duas professoras no ambiente escolar, bem como a análise e reflexão da participação docente no programa formativo, descritas em diários de aula e diários de reuniões encerrando essa etapa com uma entrevista final. Participaram do estudo, 13 professores de Educação Física da rede municipal de ensino de uma cidade do interior de São Paulo, dos quais apenas duas docentes participaram do desenvolvimento do programa formativo nas escolas. As manifestações docentes por meio do questionário e da participação no programa formativo apontaram que os professores se disponibilizam a participar dos programas de formação continuada, entretanto, as prioridades de cada professor (como: família, lazer ou outros afazeres) podem demarcar dificuldades para o estabelecimento de momentos comuns a todos os docentes, impossibilitando a participação efetiva dos professores dentro dos programas de formação...
Keywords: Circos; Educação fisica; Formação profissional; Educação física - Estudo e ensino; Formação continuada; Abordagem interdisciplinar do conhecimento; Circus